PENGKAJIAN BERBAGAI KONSENTRASI RAGI ROTI UNTUK PERTUMBUHAN PLANLET TEBU Saccharum spp var PS 61 IN VITRO - Edy Setiti Wida Utami; Dwi Setyo Rini; Eka Sugiyarta (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2001)
This experiment was expect for the find of alternative substitution of dalapon’s herbicide, its have active materials as 2,2 dichloropropionat acid. The fuction of dichloropropionat is very important on the differentiation and growing of sugarcane plantlet. The purpose of the research was to know the effect some concentration of Baker’s yeast that consist Saccharomyces cereviceae to growth of sugarcane (Saccharum spp) var PS61 plantlet. This experiment was arranged in a Completely Randomized Design with eight treatments and four replications. The treatment were: (K) control; (Po) without dalapon’s herbicide and Baker’s yeast; (0.25 g/l) medium; Bakers yeast 0.5 g/l medium; (P0.75) g/l medium; (P1.0) Baker’s yeast 1.0 g/l medium; (P1.25) Baker’s yeast 1.25 g/l medium; (P1.5) Baker’s yeast 1.5 g/l medium. The observation was done by destruction of the media every two weeks until the twelve weeks to the height of shoots, and length of primary roots. The result of this experiment showed that the application of Baker’s yeast media could be increasing the heigh of shoots and the length of primary roots. Concentration of Baker’s yeast that the suitable for growing of the sugarcane plantlet is 0.25 mg/l.